The Effect of Virtual Reality Simulation Training to Improve Disaster Preparedness for Cadre in Bandung West Java, Indonesia - Calisanie, Nyayu Nina Putri; Tukimin, Tukimin; Dioso, Regidor III; Puspasari, Susy; Nurhayati, Nunung; Permana, Septa; Lindayani, Linlin (The Malaysian Journal of Nursing (MJN), 2025)
Background: Despite improved governmental disaster management efforts, household preparedness remains insufficient, leaving communities vulnerable. Cadres are pivotal in promoting disaster preparedness at the grassroots level. Virtual Reality Simulation (VRS) offers novel approaches to improve training in disaster response by creating immersive, interactive environments that enhance skill acquisition. Objective: This study aims to assess the effectiveness of VRS training on improving disaster preparedness among Indonesian cadres, comparing outcomes with a control group receiving no such intervention. Methods: A quasi-experimental design with a control group and repeated measures was implemented in Bandung Regency, West Java. A total of 400 cadres participated, divided equally between the intervention group receiving VRS training and a control group. Disaster preparedness was measured using the Household Emergency Preparedness Scale (HEPS). Data analysis involved ANOVA and Generalised Estimating Equations (GEE) to compare preparedness scores across time points. Results: The intervention group demonstrated significant improvements in disaster preparedness scores post-intervention and at one-month follow-up (p<0.001), with a moderate effect size (Cohen's d = 0.41). The control group showed no significant change over time. GEE analysis confirmed a statistically significant increase in preparedness scores for the intervention group after controlling for baseline differences (ß = 10.2, p<0.001). Conclusion: VRS training effectively enhances disaster preparedness among community health cadres by providing a scalable and immersive approach to improving disaster readiness. VR-based training presents a viable alternative to traditional methods, especially in resource-limited areas, with potential for widespread implementation in disaster-prone regions.